Trafficking in Women and Children in Nigeria: A Human Right Discourse - Okoye, Chioma Okeoma (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2025)
Trafficking in women and children is a serious violation of human rights, stripping victims of their dignity, freedom, and security. It’s a global crisis that thrives on vulnerability, coercion, and exploitation, often forcing people into labor, sexual slavery, or other forms of abuse. This study therefore examined the issue of trafficking in women and children within the broader context of human rights discourse. It explores the protection afforded to victims under the Nigerian Constitution and international human rights laws, with a particular focus on gender equity. The study highlights fundamental rights such as the right to life, liberty and security, dignity of the human person, and freedom of movement as enshrined in legal instruments. It further investigates the enforcement mechanisms available to trafficking victims, as well as the practical challenges that hinder the realization of these rights. These include lack of coordination among law enforcement agencies, difficulties in prosecution, witness intimidation, victims’ reluctance to testify, inducement by traffickers, and the complex, syndicate-based structure of trafficking networks. The study also provides a comparative perspective by examining approaches to trafficking in other jurisdictions and discusses the limitations posed by inadequate legal provisions and procedural rules. Emphasis is placed on the need to adopt more effective international mechanisms and legal reforms to strengthen the enforcement of anti-trafficking laws. Finally, the research addresses the jurisdictional reach of Nigerian courts in handling trafficking-related cases. Through this multidisciplinary approach, the study underscores the urgency of a coordinated, rights-based, and gender-sensitive response to trafficking in women and children.